Research methods for business : - Sekaran, Uma (John Wiley & Sons Ltd, 2016)
This book offers students practical perspectives on how research can be applied in real business situations. The seventh edition has been fully revised and updated to include cutting-edge examples and enriched pedagogical features designed to improve student learning outcomes. There is now an increased emphasis on the relationship between the scientific and the pragmatic approaches to research, while the key concepts are explored and applied to real-life research throughout the book.